A máquina aconselha, o ser humano decide? Inteligência artificial e responsabilidade científica - Emerson Willian Santos de Almeida (Online Brazilian Journal of Nursing, 2026)
With the advent of artificial intelligence (AI) and its developments, various concerns have also arisen. Nevertheless, this rapid advance has optimized processes and made it possible to overcome stages that once required excessive time or became obsolete in the face of new technological possibilities. This milestone also encompasses the extinction of some professions and the appreciation or rise of others.